Tailoring therapy for heart failure: the pharmacogenomics of adrenergic receptor signaling - Femminella GD; Barrese V; Ferrara N; Rengo G (Dove Medical Press, 2014)
Grazia Daniela Femminella,1 Vincenzo Barrese,2,3 Nicola Ferrara,1,4 Giuseppe Rengo4 1Department of Translational Medical Sciences, Federico II University, Naples, Italy; 2Department of Neuroscience, Reproductive Science and Odontostomatology, Federico II University, Naples, Italy; 3Division of Biomedical Sciences, St George’s University of London, London, UK; 4”Salvatore Maugeri” Foundation – IRCCS – Scientific Institute of Telese Terme, Telese Terme, Benevento, Italy Abstract: Heart failure is one of the leading causes of mortality in Western countries, and β-blockers are a cornerstone of its treatment. However, the response to these drugs is variable among individuals, which might be explained, at least in part, by genetic differences. Pharmacogenomics is the study of genetic contributions to drug response variability in order to provide evidence for a tailored therapy in an individual patient. Several studies have investigated the pharmacogenomics of the adrenergic receptor system and its role in the context of the use of β-blockers in treating heart failure. In this review, we will focus on the most significant polymorphisms described in the literature involving adrenergic receptors and adrenergic receptor-related proteins, as well as genetic variations influencing β-blocker metabolism. Keywords: adrenergic system, polymorphisms, β-blockers, functional recovery